PEMBERIAN RESTITUSI SEBAGAI UPAYA PERLINDUNGAN HUKUM BAGI ANAK KORBAN TINDAK PIDANA PERDAGANGAN ORANG - Rini Anggreini; Madiasa Ablisar; Muhammad Ekaputra; Chairul Bariah (USU LAW JOURNAL, 2019)
ABSTRACT   One of the forms of conflicts encountered in the community is the crime of human trafficking which can be categorized as modern slavery. Children who became victims of the criminal acts of trafficking such person need to be protected because a criminal offence against a child not only cause physical or psychological suffering that affect the growing of cotton and the quality of life of the child but also raises materially disadvantage or immateriil. Basically there are forms – form or model protection can be given to children as victims of trafficking which one is granting Restitution. There are rights that are owned by children of various legal instruments and rules that exist. The fulfillment of the rights of the child is also the protection of the law as an attempt to advance the child if the child is a victim of a criminal offence. One of the efforts of the legal protection and rights that is owned by a son who became a victim of a criminal act is a right to obtain restitution. In the Presidential Regulation Number 43/2017 about implementation of Restitution for child as a crime victims set up one about the mechanism of filing the Restitution. Filing a restitution mechanism can be divided into two stages, namely submitted at the stage of investigation and prosecution. In addition the application for restitution can also be submitted following the verdict of the Court. Various barriers or legal issues are still found in the Presidential Regulation Number 43/ 2017.   Keywords               :  Restitution, legal protection, children, Human Trafficking